PENDIDIKAN AGAMA: MENJAWAB TANTANGAN MODERNISASI - Jihan Abdullah (Hunafa: Jurnal Studia Islamika, 2006)
Modernization often creates a paradigm and new values. Therefore, people who envlove in it including learners are faced with two facts; whether they are resistennt when interacting with it  or accept it with all its consequences. Based on this, we need supreme morality to  prevent or at least to  descrease secularism- in many occations-  is produced by modernization.Within this context, Islamic education which has for long time been taught to students at schools,  seems less able to-in many cases- save students’ morality without disregarding external factors, of course. So, what’s actually wrong with our Islamic education. Kata Kunci:     Modernisasi, pendidikan agama, perubahan kurikulum